Analysis of Prostate Cancer Incidence Based on Body Mass Index and Blood Pressure Factors - Sabna Ayu Sagita Berliana; Yuni Prastyo Kurniati (Journal La Medihealtico, 2025)
Prostate cancer is one of the most common cancers in men worldwide and ranks fourth according to GLOBOCAN 2022. Its incidence in Asia, including Indonesia, continues to increase each year. Prostate cancer risk factors include both modifiable variables like blood pressure and body mass index (BMI) and non-modifiable variables like age and family history. This study aimed to determine the association between BMI and blood pressure with the incidence of prostate cancer. This study employed an analytical observational design using a retrospective hospital-based case-control approach. A total of 68 samples were collected, comprising 22 patients with benign prostatic hyperplasia (BPH) as the control group and 46 patients with prostate cancer as the case group. BMI and blood pressure data were collected from medical records and categorized based on the classifications from the WHO and PERHI (2019). The chi-square test was employed for the bivariate analysis with a significance level of p < 0.05. There was no significant associationfound between blood pressure and the incidence of prostate cancer (p = 0.304), while there was a significant association between BMI and the risk of prostate cancer (p = 0.023). The OR value of 0.581 with a 95% CI (0.205–1.645) indicated that blood pressure was not a statistically significant factor. These findings imply that hormonal alterations, persistent inflammation, and elevated insulin-like growth factor 1 (IGF-1) activity may raise the risk of prostate cancer in overweight individuals. In conclusion, BMI shows a significant association with prostate cancer incidence, whereas blood pressure does not demonstrate a significant association.